Rational prescribing in paediatrics in a resource-limited setting. Issue 7 (9th May 2013) - Risk, Rachel; Naismith, Hamish; Burnett, Alexander; Moore, Sophie E; Cham, Mamady; Unger, Stefan
Abstract : Introduction: There is evidence of inappropriate medication use, causing unnecessary costs for health systems, particularly those with limited resources. Overprescription is commonly reported and can lead to antibiotic resistance. Prescribing patterns differ between countries; little is known about paediatric prescribing practices in Africa. Objectives: To investigate prescribing practices in children in The Gambia, West Africa. Method: A retrospective survey of prescribing practices in children under 5 years of age based on WHO protocol DAP/93.1 was conducted. Twenty government-run health centres across all six regions in The Gambia were assessed. The first 10 encounters each month in 2010 were recorded. For each encounter, patient demographics, diagnoses and medications were recorded as per protocol. Results: Two thousand and four hundred patient encounters were included. The mean number of medications per encounter was 2.2 (median 2.0, IQR 2.0–3.0). Across different geographical regions within The Gambia antibiotics were prescribed in 63.4% (IQR 62.8–65.8%) and micronutrients in 21.7% (IQR 15.3–27.1%) of patient encounters. There was evidence of high antibiotic prescription in children with cough and coryzal symptoms (54.5%; IQR 35.8–59.0%) and simple diarrhoea without dehydration (44.8%; IQR 36.7–61.3%). 74.8% (IQR 71.8–76.1%) of medications were prescribed generically. Conclusions: The study showed an overprescription of antibiotics and substantial usage of micronutrients despite a lack of international evidence-based guidelines. Cost-effective interventions to improve prescribing practices are called for and more studies with a focus on rational prescribing in paediatrics in low-income settings are urgently required to fill the gap in current knowledge.